Correlations of Gene Variants LEP rs2167270, LEPR rs1137100, GHRL rs696217, rs27647, and NPY rs16147 with Obesity and Adolescent Eating Behavior: Case-Control Study - Olga V. Kochetova; Ziliya A. Shangareeva; Tatyana V. Viktorova; Gulnaz F. Korytina; Vitaliy V. Viktorov ("Paediatrician" Publishers LLC, 2022)
Background. Childhood obesity is topical global healthcare issue. The correlations between variable regions of genes encoding leptin and its receptor, ghrelin and neuropeptide Y, and the risk of obesity development in children have not been confirmed completely. Mechanisms for implementing such correlation via the influence of genes on children's behavior remain unexplored.Objective. The aim of the study is to examine the correlation between leptin, leptin receptor, ghrelin and neuropeptide Y gene variants and obesity in adolescents and their eating behavior.Methods. The study included children aged from 10 to 18 years with exogenous constitutive obesity and normal body weight. Variants in genes for leptin LEP rs2167270, leptin receptor LEPR rs1137100, ghrelin GHRL rs696217 and rs27647, neuropeptide Y NPY rs16147 were determined. Adolescents' eating behavior was evaluated via psychometric questionnaires DEBQ (Dutch Eating Behavior Questionnaire) and TFEQ (the Three Factor Eating Questionnaire).Results. Gene variant distribution analysis in 150 obese and 150 normal weight children has revealed correlation with obesity for the variant rs1137100 of the LEPR gene (p = 0.001). Variants rs2167270 of the LEP gene (p = 0.015), rs696217 of the GHRL gene (p = 0.040), and rs16147 of the NPY gene (p = 0.020) were associated with adolescent eating behavior predisposing to obesity.Conclusion. The leptin receptor gene variant rs1137100 is associated with obesity in adolescents, and the variants rs2167270 of the leptin gene, rs696217 of the ghrelin gene, and rs16147 of the neuropeptide Y gene are associated with changes in eating behavior.